NEO-SALAFISME DI INDONESIA - Eliza Eliza (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2015)
The emergence of the reform movement in Indonesia can not be separated from the process of natural change his mind about Islam , since the opening lines of communication with the countries of the Middle East as a center for the development of Islam . The ideas of renewal of the Middle East is , in its development , also rolled to Indonesia --- which is often regarded as Islam " periphery " . On the other hand , the social conditions of the religious life in Indonesia when it was very alarming . This was caused by colonialism and religious understanding are not in accordance with the teachings of Islam. thus reflected in the reality of social life tends to the condition of stagnation , ignorance and poverty